Building Brand Awareness and Customer Loyalty through TITIP Marketing Strategies - Cahyanti, Ichtiar Melia; Indradewa, Rhian; Abadi, Ferryal; Kustiawan, Unggul (Journal La Bisecoman, 2024)
The Indonesian on-demand delivery industry is experiencing rapid growth, fueled by the fast-paced urban lifestyle and advancements in technology. Competition in this sector is intensifying with the emergence of various platforms such as Shopee, Tokopedia, Bukalapak, and Blibli. These platforms fiercely compete to attract customers by offering a wide range of features and attractive services. This study aims to analyze the marketing plan for the on-demand delivery app, TITIP. The research methodology employed is a descriptive case study, collecting data from literature reviews, observations, and interviews with experts. Findings indicate that TITIP possesses significant potential to build brand awareness and customer loyalty through effective market segmentation, targeted marketing, and strong positioning. In conclusion, a structured and innovative marketing plan is crucial for TITIP's success in navigating the competitive landscape. Recommendations for TITIP include continuous monitoring of marketing performance, strengthening collaborations with influencers, and enhancing loyalty programs to retain existing customers and attract new ones.